2020
DOI: 10.3389/fendo.2020.571659
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Utilization by Brown Adipose Tissue: What’s Hot and What’s Not?

Abstract: Our understanding of brown adipose tissue (BAT) function in humans has increased rapidly over the past 10 years. This is predominantly due to the development of powerful non-invasive imaging techniques such as positron emission tomography that can quantify BAT mass and function using metabolic tracers. Activation of BAT during cold-induced thermogenesis is an effective way to dissipate energy to generate heat and requires utilization of multiple energy substrates for optimal function. This has led to interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…2 ). In addition to triglyceride stores, BAT sequesters and utilises several circulating substrates such as glucose, fatty acids and some amino acids during thermogenesis (reviewed in ( 23 )). Therefore, BAT activation may improve other metabolic health parameters such as hyperglycaemia and dyslipidaemia in addition to increasing energy expenditure.…”
Section: The Distribution and Function Of Brown And Beige Adipose Tissuementioning
confidence: 99%
“…2 ). In addition to triglyceride stores, BAT sequesters and utilises several circulating substrates such as glucose, fatty acids and some amino acids during thermogenesis (reviewed in ( 23 )). Therefore, BAT activation may improve other metabolic health parameters such as hyperglycaemia and dyslipidaemia in addition to increasing energy expenditure.…”
Section: The Distribution and Function Of Brown And Beige Adipose Tissuementioning
confidence: 99%
“…Mitochondrial functions and capacity can also be enhanced by brown adipose tissue, which is metabolically activated by cold exposure [ 43 , 44 ]. Recently, Kovaničová et al [ 45 ] have reported that cold-acclimatized ice-water swimmers respond to cold by non-shivering thermogenesis mediated by higher fat oxidation than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Though LDB1 may regulate Ucp1 to affect cold tolerance, reductions in additional gene targets involved in lipid metabolism and thyroid signaling (e.g., Elovl3 , Dio2 ) likely contribute to the severe cold intolerance phenotype. Substrates like glucose and fatty acids are either oxidized as fuel for thermogenesis or used to replenish intercellular lipid pools [ 34 , 35 ]. Given the importance of metabolites for adipocyte thermogenesis, models affecting substrate uptake and utilization, including an adipose triglyceride lipase (ATGL) knockout model, also result in cold intolerance phenotypes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%